White Matter Microstructure Changes in the Thalamus in Parkinson Disease with Depression: A Diffusion Tensor MR Imaging Study - Li, W.; Liu, J.; Skidmore, F.; Liu, Y.; Tian, J.; Li, K. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Depression occurs frequently in PD; however the neural basis of depression in PD remains unclear. The aim of this study was to characterize possible depression-related white matter microstructural changes in the thalamus of patients with DPD compared with those with NDPD. MATERIALS AND METHODS: FA and MD maps from DTI were obtained in 14 patients with DPD and 18 patients with NDPD. Region-of-interest−guided VBA was conducted on the FA maps to detect possible microstructural differences in the thalamus between these 2 patient groups. Moreover, mean FA and MD in regions with a detected difference were compared between DPD and NDPD groups, and correlations between diffusion quantities and the severity of depression were analyzed. RESULTS: White matter microstructure differences were found between the patients with DPD and NDPD in the bilateral mediodorsal thalamic regions. In these regions, patients with DPD showed significantly decreased FA values (P < .005) compared with patients with NDPD, and the mean values of FA were negatively correlated with the scores of depression severity (P < .05) for patients with PD. No significant differences of MD were found in the mediodorsal thalamus between these 2 groups. CONCLUSIONS: Our results provide preliminary evidence that the mediodorsal thalamus may play an important role in depression in PD and suggest a relationship between FA in the mediodorsal thalamus and the presence of depressive symptoms in patients with DPD. These findings may be helpful for further understanding the potential mechanisms of depression in PD. DPDdepressed PDDSMDiagnostic and Statistical Manual of Mental DisordersDTIdiffusion tensor imagingFAfractional anisotropyfMRIfunctional MR imagingFMRIBFunctional MR Imaging of the BrainFSLFMRIB Software LibraryHAMDHamilton Depression ScaleH-YHoehn–Yahr stagingLEDDL-dopa equivalent daily dosageMDmean diffusivityMDDmajor depressive disordermFAmean value of FAmMDmean value of MDMMSEMini-Mental State ExaminationMNIMontreal Neurological InstituteNDPDnondepressed PDNSnot significantPDParkinson diseaseUPDRSUnified Parkinson Disease Rating ScaleVBAvoxel-based analysisVBMvoxel-based morphometry